STRATEGI PEMASARAN PT. SUZUKI INDOMOBIL MOTOR DALAM EKSPOR SUZUKI ADDRESS KE EROPA TAHUN 2015 PASCA KELUARNYA KEBIJAKAN STANDAR EMISI EURO 4 - ", Rafly; Tjarsono, Idjang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aims to determine strategies PT.Suzuki Indomobil Motor in exporting Suzuki Address to European based policy euro 4 emission standards.This research included into descriptive research and the research method used was a case study, which takes an object to be studied by focusing on a single issue. Data collection techniques used by the author is the study of literature sourced from books, journals, documents and a valid website. The data in this study apply qualitative analysis techniques with deductive writing techniques. The perspective used in this research is a liberal perspective, while his theory is the theory of absolute advantage.Results from the research showed that the policy of the euro emission standards contained in the European motorcycle market influence, so as not to carelessly motorcycle Europe as be exported and marketed. Marketing strategy undertaken by PT.Suzuki Indomobil Motor to penetrate the European market under the policy by producing Suzuki Address. Suzuki Address is a scooter-type motorcycle products with international standard specifications so that it can qualify contained in the policy of the euro 4 emission standards.Keywords: Suzuki Address, Product, Skutik